The meaning of "un-recorded marriage" in the perspective of the marriage law - Endang Prasetyawati (Technium Social Sciences Journal, 2023)
Humans are zoon politicon, namely creatures that live in groups. As humans who live in groups, humans always need other people in living their lives. One of the needs of human life is to form a family and obtain offspring. This is a human right for everyone. Provisions on the right to have a family and continue offspring are regulated in Article 10 paragraph (1) of Law Number 39 of 1999 concerning Human Rights which stipulates that everyone has right to form a family and continue offspring through a legal marriage. Based on provisions in the article it can be understood that to form a family one must first marry. Marriage as an institution that is used to bind humans who are destined in two genders, namely men and women. After the marriage takes place, a family is formed. Marriage is realm of private law which cannot be separated from intervention of state, which in this case is government, on the basis reason that marriage is not just forming a family and continuing offspring, but there are far-reaching consequences for parties bound by marriage and their children born from marriage. Marriage in Indonesia is regulated in Law Number 1 (1974) concerning Marriage which has been amended by Law Number 16 of 2019 (hereinafter referred to as the Marriage Law). Unrecorded marital status does not have binding legal force because it doesn’t have an authentic certificate as proof of validity marriage. As stipulated in Law No.1 of 1974, Government Regulation No.9 of 1975, Permenag No.20 (2019) concerning Marriage Registration and Presidential Decree No.1 of 1991 concerning Compilation of Islamic Law. Status of ’Unrecorded Marriage’ on the Family Card to Protect Children and Wife. It is necessary to renew the legal registration of marriages through a contextual approach, so as to provide certainty and legal protection for husbands and wives and children born from a marriage. Socialization is needed so that people realize how important it is to register their marriage even though they have to go through a trial at the Religious Court.